The reaction-response of organism at different modes irradiation of the animals - A. I. Lypska (Ядерна фізика та енергетика)
According to the dynamic of peroxidation indexes (constituents of lipids, lipoproteins, antioxidants activity, diene conjugates and malondialdehyde) in blood plasma of rats of Vistar line the reaction-response of organism on ionizing radiation effect are determined. It is discovered that the continuously intake to organism of radionuclides produced during Chernobyl NPP accident is the most critical for the organism at the equal effective doses of radiation. The single external total irradiation of animals by γ-quanta of 137Cs leads to the lowest reaction of response.